New anti-hepatitis B virus drugs under development and evaluation. Issue 6 (December 2016) - Pan, Jiaqian; Tong, Shuangmei; Kang, Lei; Tang, Jing
Abstract : Purpose of review: Although available therapies can effectively inhibit hepatitis B virus (HBV) replication in patients with active chronic hepatitis B (CHB) infection, therapeutic efficacy is limited because of potential drug resistance, and an inability to mediate viral clearance and to rectify immune impairment in CHB patients. This review will summarize the state-of-the-art for anti-HBV drugs and focus on potential drugs and targets under development and evaluation. Recent findings: New developing drugs are evaluated for their antiviral effects in the areas of interference with the viral replication cycle, elimination of covalently closed circular DNA, modulation of host immunity and identification of the La protein and its regulator casein kinase as possible targets for the development of anti-HBV therapies. Summary: These novel compounds and targets have showed great inhibitory effects on HBV replication in vitro and in animal models. Several novel therapies are promising in early clinical trials. Potentially, combination of newly developing and current antiviral drugs may cure CHB in the clinic.